Peningkatan Kreativitas Anak Melalui Permainan Balok Roncean di PAUD Duta Ananda Kota Sawahlunto - Yetri; Ismet, Syahrul (UNIVERSITAS SERAMBI MEKKAH, 2025)
The results of field observations at PAUD Duta Ananda Kota Sawahlunto showed that children's creativity at PAUD Duta Ananda Kota Sawahlunto is still relatively incapable. This can be seen from the many children who always do all learning activities that always imitate what is exemplified by the teacher without any creative innovation produced by the children themselves. Some children prefer to play running around, some are more silent and do not want to participate in learning. This study aims to improve the development of children's creativity with Roncean block games at PAUD Duta Ananda Kota Sawahlunto. The type of research used is Classroom Action Research (CAR). The subjects in this study were children at PAUD Duta Ananda Kota Sawahlunto. The study was conducted in a class with 10 students. This study was carried out in several cycles consisting of four main stages: planning, implementing actions, observation, and reflection. Based on the research conducted, it was found that children's creativity increased through the roncean block game activities that had been carried out, which were assessed from the children's ability to express the creativity of the block ideas they formed according to their ideas in the fluency indicator, the results increased from 20% to 80%. Children's ability to move their hands quickly in arranging the roncean block game on the flexibility indicator increased from 20% to 80%. Children's ability to arrange blocks according to the desired shape imagination on the originality indicator increased from 10% to 70%. Children's ability to explain objects around them that have the same shape as the arrangement of blocks they arrange on the elaboration indicator increased from 10% to 70%.